Натхненний трудівник на ниві національного відродження України - Старовойтенко, І. (Народна творчість та етнографія, 2005)
This article is devoted to the memoirs and letters written by Yevhen Chykalenko (1861-1929) who was an active member of Ukrainian national movement at the beginning of the 20th Century, political activist, founder of Ukrainian press, and a struggler for the development of Ukrainian language during the time when Ukrainian language was repressed and national ideas unpopular. The author of the article gives a detailed overlook of the childhood and adult memoirs of Ye.Chycalenko, his family and surroundings as well as traditions of his family life style. His image corresponds to the ideal "land-lord", knowledgeable in the life and traditions of his folk.